Rights and Obligations of Husband Wife of Factory Workers in Semarang: According to Social Construction Theory - Muhammad Mustolich, Muhammad Mustolich (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2024)
Household life cannot be separated between husband and wife who have rights and obligations to each other in fulfilling them, so this must be fulfilled. The purpose of this study is to determine the extent of the application of the rights and obligations of husband and wife who work as factory workers in Semarang according to social construction theory. This research method is qualitative. This type of research is empirical, with a sociological approach, and the nature of the research is descriptive analytical. The data sources of this research include primary data obtained from observations and several interviews with people in the Semarang area. The result of this study is that with the social construction theory by Peter L. Berger, we can understand that the rights and obligations of husband and wife of factory workers in Semarang are the result of a social process involving externalization, objectivation, and internalization. Although there are challenges in terms of gender inequality and double burden, increased awareness and policy changes can help steer towards a more just and equal division of roles. Communities in the Semarang area have undergone a social construction process in which the environment is the main factor in changing the order in the family, especially in fulfilling the rights and obligations between husband and wife, but with these changes inseparable from the urgent conditions and utilizing existing potential in order to strengthen the family economy so as to make a strong household.  Kehidupan rumah tangga tidak dapat dipisahkan antara suami dan istri yang memiliki hak dan kewajiban satu sama lain dalam memenuhinya, sehingga hal ini harus dipenuhi. Tujuan dari penelitian ini adalah untuk mengetahui sejauh mana penerapan hak dan kewajiban suami istri yang bekerja sebagai buruh pabrik di Semarang menurut teori kontruksi sosial. Metode penelitian ini adalah kualitatif. Jenis penelitian ini adalah empiris, dengan pendekatan sosiologis, dan sifat penelitiannya adalah deskriptif analitis. Sumber data dari penelitian ini meliputi data primer yang diperoleh dari hasil observasi dan beberapa wawancara dengan masyarakat di wilayah Semarang. Hasil dari penelitian ini bahwa dengan teori konstruksi sosial oleh Peter L. Berger, kita dapat memahami bahwa hak dan kewajiban suami istri buruh pabrik di Semarang adalah hasil dari proses sosial yang melibatkan eksternalisasi, objektivasi, dan internalisasi. Meskipun ada tantangan dalam hal ketidakadilan gender dan beban ganda, kesadaran yang meningkat dan perubahan kebijakan dapat membantu mengarahkan menuju pembagian peran yang lebih adil dan setara. Masyarakat yang ada di daerah Semarang telah menjalani proses kontruksi sosial yang mana lingkungan menjadi faktor utama dengan adanya perubahan tatanan dalam keluarga khususnya dalam pemenuhan hak dan kewajiban antara suami dengan istri, namun dengan adanya perubahan tersebut tidak terlepas dari adanya kondisi terdesak serta memanfaatkan potensi yang ada guna untuk memperkokoh perekonomian keluarga sehingga menjadikan rumah tangga yang kokoh.